Role of Pyroptosis in Cardiovascular Diseases and its Therapeutic Implications - Zeng, Cheng; Wang, Renqing; Tan, Hongmei (International journal of biological sciences, 2019)
Pyroptotic cell death or pyroptosis is characterized by caspase-1-dependent formation of plasma membrane pores, leading to the release of pro-inflammatory cytokines and cell lysis. Pyroptosis tightly controls the inflammatory responses and coordinates antimicrobial host defenses by releasing pro-inflammatory cellular contents, such as interleukin (IL)-1β and IL-18, and consequently expands or sustains inflammation. It is recognized as an important innate immune effector mechanism against intracellular pathogens. The induction of pyroptosis is closely associated with the activation of the NOD-like receptor 3 (NLRP3) inflammasome which has been linked to key cardiovascular risk factors including hyperlipidemia, diabetes, hypertension, obesity, and hyperhomocysteinemia. Emerging evidence has indicated pyroptosis as an important trigger and endogenous regulator of cardiovascular inflammation. Thus, pyroptosis may play an important role in the pathogenesis of cardiovascular diseases. Design of therapeutic strategies targeting the activation of NLRP3 inflammasome and pyroptosis holds promise for the treatment of cardiovascular diseases.